Nutritional Insights: How Food Choices Affect Atrial Fibrillation - Gondko, Daniel; Dębiec, Patrycja; Roman, Jakub; Pietrzak, Nikodem (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Atrial fibrillation (AF) is a prevalent cardiac rhythm disorder that significantly impacts global health. Emerging evidence suggests that dietary habits play a crucial role in the modulation and management of AF. This review article aims to synthesize current knowledge on the interplay between nutrition and atrial fibrillation, providing insights for healthcare professionals and patients alike in managing this condition through dietary choices. State of Knowledge: Various studies have examined the effects of specific nutrients, food groups, and dietary patterns on the incidence and progression of AF. This review delves into research linking macro- and micronutrients—such as omega-3 fatty acids, fiber, and antioxidants—to AF risk. It also evaluates the influence of dietary patterns, including Mediterranean and plant-based diets, on the electrical and structural remodeling of the heart that predisposes to AF. Additionally, the impact of excessive alcohol and caffeine consumption on AF is scrutinized, highlighting the importance of moderation. Summary: The evidence indicates a significant association between diet and atrial fibrillation, suggesting that specific dietary modifications could potentially reduce AF risk or mitigate its severity. Recommendations for clinical practice involve promoting heart-healthy dietary patterns, focusing on the balance and quality of nutrients, while considering individual dietary restrictions and preferences. Further research is needed to clarify causal relationships and to develop comprehensive dietary guidelines specific to AF management.